Astragaloside IV alleviates heart failure via activating PPARα to switch glycolysis to fatty acid β-oxidation - Zhiwei Dong (Nature Portfolio, 2017)
Abstract In heart failure (HF), energy metabolism pathway in cardiac muscle changes from fatty acid β-oxidation to glycolysis. However, the exact mechanism is unknown. Sarcoendoplasmic reticulum Ca2+α ATPase (SERCA) expression is downregulated and mitochondrial function is reduced in HF, perhaps partly due to a substantially reduced energy supply for excitation–contraction coupling resulting from a lower fatty acid β-oxidation rate. We investigated whether Astragaloside IV can activate peroxisome proliferator-activated receptor alpha (PPARα) to stimulate fatty acid β-oxidation and increase cardiac energy production, improving mitochondrial function and the efficiency of SERCA in HF. In pressure overload-induced HF mice and isolated hypertrophic myocardial cells, fatty acid β-oxidation and heart function were substantially strengthened following Astragaloside IV treatment, as demonstrated by the increased expression of PPARα and SERCA2a. In vitro, Astragaloside IV regulated energy metabolism by increasing ATP production and enhancing mitochondrial function, attributable to increased oxygen consumption and slightly increased mitochondrial Ca2+ uptake. In HF, Astragaloside IV switched glycolysis to fatty acid β-oxidation, as confirmed by reduced anaerobic glycolysis and an increased oxygen consumption ratio. These results suggest that Astragaloside IV can stimulate fatty acid β-oxidation and improve mitochondrial function, which may present a novel cardioprotective treatment that inhibits the progress of HF.